2019
DOI: 10.1111/socf.12507
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Homosexuality in 88 Countries: Education, Political Freedom, and Liberalism

Abstract: Researchers have repeatedly found a positive correlation between education and tolerance. However, they may be victims of an unrepresentative sample containing only rich Western liberal democracies, where political agendas have a liberalizing effect on curricula. In this paper, we specify the relationship between education and liberal attitudes by analyzing data on educational attainment and tolerance of homosexuality (one dimension of liberalism) drawn from a heterogeneous sample of 88 countries over the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…These enhanced cognitive abilities purportedly lead to lower levels of outgroup prejudice and more liberal attitudes generally (Adorno et al 1950; Altemeyer 1996; Bobo and Licari 1989; Hyman and Wright 1979; Jost et al 2003). This view is commonly known as the “cognitive hypothesis.” Other scholars endorse a “socialization hypothesis” that argues change is contingent on the transmission of norms, commonly through a particular field of study (Dey 1996; Sidanius et al 2003; Weil 1985; Zhang and Brym 2019). In this view, fields of study act as subcultures with implicit normative approaches promoted through curricular content (Ladd and Lipset 1975; Parker et al 2016; Sidanius et al 2003).…”
Section: Higher Education and Moral Changementioning
confidence: 99%
See 1 more Smart Citation
“…These enhanced cognitive abilities purportedly lead to lower levels of outgroup prejudice and more liberal attitudes generally (Adorno et al 1950; Altemeyer 1996; Bobo and Licari 1989; Hyman and Wright 1979; Jost et al 2003). This view is commonly known as the “cognitive hypothesis.” Other scholars endorse a “socialization hypothesis” that argues change is contingent on the transmission of norms, commonly through a particular field of study (Dey 1996; Sidanius et al 2003; Weil 1985; Zhang and Brym 2019). In this view, fields of study act as subcultures with implicit normative approaches promoted through curricular content (Ladd and Lipset 1975; Parker et al 2016; Sidanius et al 2003).…”
Section: Higher Education and Moral Changementioning
confidence: 99%
“…This view is commonly known as the "cognitive hypothesis." Other scholars endorse a "socialization hypothesis" that argues change is contingent on the transmission of norms, commonly through a particular field of study (Dey 1996;Sidanius et al 2003;Weil 1985;Zhang and Brym 2019). In this view, fields of study act as subcultures with implicit normative approaches promoted through curricular content (Ladd and Lipset 1975;Parker et al 2016;Sidanius et al 2003).…”
Section: Higher Education and Moral Changementioning
confidence: 99%
“…Usually, researchers expect that increasing educational levels is accompanied by an increasing tolerant attitude. However, an analysis of the tolerance to nontraditional behavior in democratic and authoritarian societies using the World Value Survey Database shows the negative effect of authoritarian governments on the relationships between education and tolerance [Zhang, Brym, 2019]. Contemporary Russia may have this negative link too due to its non-liberal political regime.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on this conceptual bifurcation, research has found that right-wing ideologies are associated with increased prejudicial attitudes toward stigmatized groups, e.g., sexual minorities (Hoyt and Parry, 2018), with intergroup contact with stigmatized people exacerbating this effect (Hodson and Busseri, 2012). In contrast, liberalism typically correlates with accepting a greater diversity of life choices, including the choices of stigmatized groups (Zhang and Brym, 2019).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%